Nanotechnology and public health - Ferdi Tanır (Turkish Society of Public Health Specialists, 2015)
Nanotechnology is a new revolution in technology; being used in different parts of life such as self-cleaning paints, dirt repellent fabrics, the destruction of cancer cells without harming the person, biosensors that can detect even a single bacterium, odorless socks due to the destruction of bacteria, germ-free refrigerators, disinfection etc. In this article, we consider in the perspective of public health the possible risks of this new technology, which is starting to appear in all areas of our daily lives.